2021
DOI: 10.15575/biodjati.v6i2.13191
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plant Growth Promoting Rhizobacteria (PGPR) on Capcissum annum

Abstract: Plant Growth Promoting Bacteria Rhizobacteria (PGPR) is one of the potential bacteria to enhance of Capsicum annuum through inhabitation the growth of pathogenic fungi. This study aimed to characterize PGPR in chili plants (Capsicum annuum). PGPR was isolated from the soil habitat of the red chili plant in Cilegon, Indonesia. Screening was then carried out with the dual culture method on Petri dishes and tested through in vivo method on the red chili plant. The selected bacteria were characterized morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…In response, Suriani et al [12] found that simultaneous application of piper leaf extracts and PGPR inhibited blast disease and improved the growth of red rice in Bali. Several studies of PGPR have been conducted for chili [35][36][37]. For example, Thilagar et al [36] reported that in pot trials, PGPR application increased soil phosphorus levels and produced indoleacetic acid and siderophores, which promoted plant height and stem girth growth in chili.…”
Section: Productivity and Sustainabilitymentioning
confidence: 99%
“…In response, Suriani et al [12] found that simultaneous application of piper leaf extracts and PGPR inhibited blast disease and improved the growth of red rice in Bali. Several studies of PGPR have been conducted for chili [35][36][37]. For example, Thilagar et al [36] reported that in pot trials, PGPR application increased soil phosphorus levels and produced indoleacetic acid and siderophores, which promoted plant height and stem girth growth in chili.…”
Section: Productivity and Sustainabilitymentioning
confidence: 99%
“…Perakaran bambu juga banyak mengandung bakteri pelarut fosfat Pseudomonas fluorescens, yang berperan dalam meningkatkan kelarutan fosfat dari dalam tanah sehingga mudah diserap dan tersedia bagi tanaman (Yulistiana et al 2020). Sari et al (2021) menjelaskan bahwa ketersediaan unsur hara dipengaruhi oleh jenis akar bambu yang mempunyai kandungan PGPR yang tinggi. PGPR menyebabkan pertumbuhan tanaman meningkat, karena disebabkan oleh peningkatan penyerapan hara mineral, peningkatan produksi fitohormon, dan penyerapan nitrogen bebas dari udara (Khanna et.…”
Section: Hasil Dan Pembahasanunclassified